Analisis Faktor Penyebab Kesulitan belajar PPKn Kelas V SDN 19 Sirenja - Lapohea, Arief Rahman; Herlina, Herlina; Firmansyah, Arif; Muchdar, Muchdar (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2025)
The problem in this study is what are the difficulties in learning PPKn for grade V students of SDN 19 Sirenja? and how to overcome the learning difficulties of PPKn grade V students of SDN 19 Sirenja?. The purpose of this study is to identify learning difficulties in PPKn class V SDN 19 Sirenja and to find out how to overcome learning difficulties in PPKn class V SDN 19 Sirenja. This type of research is qualitative research. The data collection in this study is interviews, observations, and documentation related to student learning difficulties. Data analysis techniques in qualitative research are carried out during data collection, and after the completion of data collection in a certain period. The results of this study are known to describe the learning difficulties of the students studied, most of whom are difficult to understand the material, difficulty understanding the learning media, lack of concentration, lack of attention in learning, slowness when processing learning materials, difficulty understanding sentences, unclear intonation, low learning outcomes.